(untitled) (CAHIERS MAGELLANES-NS, 2024)
The pharmaceutical industry plays a critical role in healthcare systems worldwide, contributing to the development of life-saving drugs and therapies. Evaluating the financial performance of pharmaceutical companies is crucial for stakeholders, including investors, analysts, and regulators. This study aimed to conduct a comprehensive financial analysis of [company name], a leading pharmaceutical firm, using a range of financial ratios and industry-specific metrics. The research examined profitability, liquidity, solvency, and operational efficiency ratios, as well as indicators such as research and development (R&D) intensity and patent metrics. The analysis incorporated comparative benchmarking against industry standards and peer companies to identify strengths, weaknesses, and areas for improvement. Furthermore, the study considered external factors, including regulatory changes, market conditions, and industry trends, to provide a holistic understanding of the company's financial performance. The findings of this research offer valuable insights for decision-makers and contribute to the existing literature on financial performance evaluation in the pharmaceutical sector.